Activation of Viruses by Host Proteases (Springer International Publishing, 2018)
This book will give an overview on viruses undergoing proteolytic activation through host proteases. The chapters will be organized in three themed parts, the first part describing respective viruses and their characteristics in detail. In the second part the molecular and cellular biology of the proteases involved as well as their physiological functions will be further explored. The third part will contain a chapter on protease inhibitors that are promising tools for antiviral therapy. This book will engage scholars in virology and medical microbiology as well as researchers with an interest in enzymology and protein structure and function relationship.